Organ donation: a study of the willingness of University Technology Mara (UiTM) Kedah students to donate their organs / Ariati Zakaria and Nur Syahadah Shamsul Amri - Zakaria, Ariati; Shamsul Amri, Nur Syahadah (2014)
Organ donation among the world community today is not a new phenomenon. The noble act of organ donation by donors that at times, has no blood relations has enabled many patients to have their second chance in living. Malaysia according to several studies conducted was among the lowest country in term of organ donation rate although there are abundant of patients listed for organ transplants. The citizens especially UiTM Kedah students have the problems in willingness to donate organs. There are a lot of factors that influences the willingness of UiTM Kedah students to donate their organs. Those are perception of UiTM Kedah towards organ donation, knowledge about organ donation, and religion influences on the decision to donate organ. Thus, this study examines the willingness of UiTM Kedah students to donate organ. The sample of 270 respondents of UiTM Kedah students from 9 courses will be selected. The questionnaire will be divided equally according to their courses and 30 respondents from each group is selected. Proportionate stratified random sampling technique will be used in this study and Cronbach Alpha, Descriptive statistic as well as Pearson Correlation will be used to gain data. It is hoped that researcher will gain an adequate knowledge pertaining factors that lead to lack of organ donation and what factors that influences more towards lack of organ donation